On Technology Innovations, Digitalisation and Social Security in the 21st Century. Interview with Henning Meyer - Henning Meyer (Communication Today, 2025)
The interview focuses on Henning Meyer’s view on technology and digitalisation in the terms of jobs and social security. It deals with insecurity of the technology age where the people are not capable of comprehending the fast development. While discussing the topic, Henning Meyer presents his view on the possible solutions to the insecurity in the meaning of job or activity guarantee. The interview also addresses issues of education in the technology era. At the same time, it focuses on the recent crises in Europe – including refugee crisis, the Brexit and ‘Eurozone’ crisis with the focus on the role of social democracy in these crises.